Odpowiedź :
Odpowiedź:
[tex]a)\ \ \sqrt{\frac{64}{81}}=\frac{8}{9}\\\\b)\ \ \sqrt{0,0144}=\sqrt{\frac{144}{10000}}= \sqrt{\frac{9}{625}}=\frac{3}{25}\\\\c)\ \ \sqrt{3\frac{1}{16}}=\sqrt{\frac{49}{16}}=\frac{7}{4}=1\frac{3}{4}\\\\d)\ \ \sqrt[3]{125000}=\sqrt[3]{50^3}=50\\\\e)\ \ \sqrt[3]{\frac{27}{64}}=\frac{3}{4}\\\\f)\ \ \sqrt[3]{-3\frac{3}{8}}=\sqrt[3]{-\frac{27}{8}}=-\frac{3}{2}=-1\frac{1}{2} [/tex]
[tex]\sqrt{\frac{64}{81}} = \frac{\sqrt{64}}{\sqrt{81}} =\frac{\sqrt{8^{2}}}{\sqrt{9^{2}}}=\frac{8}{9}\\\\\\\sqrt{0,0144} = 0,12\\\\\\\sqrt{3\frac{1}{16}} = \sqrt{\frac{49}{16} } = \frac{\sqrt{49}}{\sqrt{16}} = \frac{7}{4} = 1\frac{3}{4}\\\\\\\sqrt[3]{125000} = 50\\\\\\\sqrt[3]{\frac{27}{64}} = \frac{\sqrt[3]{27}}{\sqrt[3]{64}} = \frac{3}{4}\\\\\\\sqrt[3]{-3\frac{3}{8}} = \sqrt[3]{-\frac{27}{8}} = \sqrt[3]{(-\frac{3}{2})^{3}}} = -\frac{3}{2} = -1\frac{1}{2}[/tex]